2012
DOI: 10.1177/1476718x11430076
|View full text |Cite
|
Sign up to set email alerts
|

To separate or not to separate? Parental decision-making regarding the separation of twins in the early years of schooling

Abstract: In recent times concerns about possible adverse effects of early separation and advocacy for individual rights have resulted in a movement away from organizational level policies about the separation of twin children as they enter school. Instead, individualized approaches that focus on the twin children’s characteristics and family perspectives have been proposed. This study, conducted in Australia where all but a few families had choice about the class placement of their twin children, questioned parents (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 32 publications
0
11
0
16
Order By: Relevance
“…Schools may have a set policy regarding classroom placement of twins (Saudino et al, 2005), depending on national context and beliefs of the principle and teachers. Nevertheless, most young twins and their parents prefer not to be separated (Gordon, 2015; Staton et al, 2012). The protective effect of classroom sharing regarding victimization for girl–girl twins should be taken into account when twins enter primary school.…”
Section: Discussionmentioning
confidence: 99%
“…Schools may have a set policy regarding classroom placement of twins (Saudino et al, 2005), depending on national context and beliefs of the principle and teachers. Nevertheless, most young twins and their parents prefer not to be separated (Gordon, 2015; Staton et al, 2012). The protective effect of classroom sharing regarding victimization for girl–girl twins should be taken into account when twins enter primary school.…”
Section: Discussionmentioning
confidence: 99%
“…For most twin pairs, staying together in the first year of school is a social support (Bekkhus et al, 2011;Staton et al, 2012). Epigenetics Birth weight Birth weight is associated with epigenetic differences in genes associated with growth, metabolism, and cardiovascular function (Gordon et al, 2011;Saffery et al, 2012).…”
Section: Randomized Controlled Trialmentioning
confidence: 99%
“…For most twin pairs, staying together in the first year of school is a social support (Bekkhus et al, 2011;Staton et al, 2012).…”
Section: Issues Specific To Twinsmentioning
confidence: 99%
“…(Sipes & Sipes, 1998, pp. 159-162) Studies of twins in different countries have reported various rates of twin school separation with 31% of twins in the United Kingdom (Twins and Multiple Births Association, 2009), 19% to 48% of Dutch twins (Polderman et al, 2010;van Leeuwen, van den Berg, van Beijsterveldt, & Boomsma, 2005), 23% to 60% of Australian twins (Gleeson, Hay, Johnston, & Theobald, 1990;Staton, Thorpe, Thompson, & Danby, 2012), and 80% to 84% of American twins (National Organization of Mothers of Twins Clubs [NOMOTC], 2010;Segal & Russell, 1992) placed in independent classes. Parents of twins have reported that while some principals are willing to accept joint classroom placement requests, many principals favor class separation and some set strict twin separation policies (NOMOTC, 2010;Preedy, 1999;Segal & Russell, 1992;Twins & Multiple Births Association, 2009).…”
Section: Background and Rationalementioning
confidence: 99%
“…Additional school surveys have documented that many administrators enforce strict mandatory separation of twins in schools (Gleeson et al, 1990;Lacina, 2010;Schorn, 2009;Segal, 2011;Segal & Russell, 1992). For a sensible array of reasons, some parents of twins do prefer for their twins to be placed in separate classrooms (Friedman, 2008(Friedman, , 2010Schorn, 2009;Segal & Russell, 1992;Staton et al, 2012), but many other parents strongly favor joint placement (Alt, 2004c, p. 20;Grimes, 2006) and experience immense frustration when they are told that their twins must be separated (Bellafante, 2006;Dean, 2002;Dolan, 2012;Grime, 2008;Lacina, 2010).…”
Section: Background and Rationalementioning
confidence: 99%